PREDICTIVE MODELS FOR RESPONDER STRATIFICATION AND DRUG EFFICACY (Journal of Medical & Health Sciences Review, 2025)
Background: The Predictive models for responder stratification and drug efficacy are novel in the context of modern medicine. They have the potential to treat patients on an individualized level by considering their clinical and genetic information. Such models aim to capture the therapeutic response of patients based on specific drug therapies. The primary intent is to decrease adverse effects while improving the efficacy of treatment. There is a significant shift in interest and progress concerning predictive modeling; however, its integration and practical implementation face numerous obstacles such as data integrity, interpretability, and scarcity.  Objective: This research seeks to appreciate the explanatory factors related the effectiveness of predictive models in drug efficacy and responder stratification. For this purpose, the study analyzes the public perception as well as the integration of the genetic and demographic data. The research identifies the barriers to the use of such predictive models in day-to-day clinical practice. The study also investigates the public trust levels regarding the use predictive technologies in healthcare and the correlated outcomes regarding healthcare service delivery.  Methods: Using an online survey, data was collected from a sample of 176 participants possessing a varied background and experience with healthcare technology. The survey incorporated inquiries regarding the respondents’ knowledge of the predictive models, their assessment of the models’ effectiveness, and the personal experiences concerning drug therapies purportedly guided by such models. Quantitative data was processed using descriptive statistical methods, while qualitative data was processed with thematic analysis. The purpose of the research sought to understand the benefits and problems predictive models present in drug choice and responder stratification.  Results: The collected data suggests that although most participants possess basic knowledge of predictive models, their appreciation of such models' potential and impact on drug efficacy is limited. As many as 68% of participants reported believing that predictive models are either “very effective” or “somewhat effective” at improving drug outcomes. Nonetheless, 32% were skeptical about reliability, especially in actual clinical environments. Moreover, while the incorporation of demographic and genetic information was deemed vital for enhancing model accuracy, issues concerning data availability, model transparency, and openness-with regard to the data used, also emerged as significant concerns.Conclusion: This study underscores the potential value of predictive models for improving drug efficacy and responder stratification while also pinpointing risks to their adoption related to data, model interpretability, and public trust. The results indicate that raising public awareness and tailoring accessibility would greatly amplify the impact on patient outcomes. Subsequent work needs to tackle these problems as well as develop methods to further integrate predictive models into clinical workflows in order to sustain their usefulness in personalized medicine.